2023
DOI: 10.1039/d3ce00108c
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic study on the structure–property relationship of flexible organic crystals

Abstract: Flexible crystals have attracted extensive attentions for their potential as smart materials, such as flexible field-effect transistors, wearable devices and flexible displayers. Developing flexible materials with specific properties still remains...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…S19†). 62–64 Nanoindentation on the (010) plane showed that the elastic modulus ( E ) and hardness ( H ) of crystals of form I are E = 6.18 ± 0.01 GPa and H = 0.37 ± 0.02 GPa (Fig. S26†), which places the CTBB crystals in the category of soft materials.…”
Section: Resultsmentioning
confidence: 99%
“…S19†). 62–64 Nanoindentation on the (010) plane showed that the elastic modulus ( E ) and hardness ( H ) of crystals of form I are E = 6.18 ± 0.01 GPa and H = 0.37 ± 0.02 GPa (Fig. S26†), which places the CTBB crystals in the category of soft materials.…”
Section: Resultsmentioning
confidence: 99%
“…Flexibility is an important basis for crystals to maintain crystal integrity in response to various stimuli. 39 Here, the flexibility of AP was first investigated under a stereomicroscope (Figure 2a−c). It turned out that the crystal could be easily bent into a ring shape, and when the force was withdrawn, it would quickly return to its initial straight state (Movie S1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Flexibility is an important basis for crystals to maintain crystal integrity in response to various stimuli . Here, the flexibility of AP was first investigated under a stereomicroscope (Figure a–c).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, researchers have studied multifunctional molecular crystals. ,, Polymorphic crystals contain the same molecules arranged in different geometries within their unit cells, resulting in , significant differences in properties such as shape, color, melting point, and solubility. For example, 5-methyl-2-[(2-nitrophenyl)­amino]-3-thiophenecarbonitrile has been reported to have seven polymorphs with different colors (e.g., red, orange, and yellow) and shapes (e.g., needle, prism, and plate).…”
Section: Introductionmentioning
confidence: 99%